Heat-stable enterotoxin induced apoptosis in small intestine epithelial cells via mitochondrial oxidative phosphorylation pathway - Hou, Meijia; Yang, Wei; Liu, Nian; Sun, Simeng; Feng, Qizheng; Shi, Bo; Liu, Jiali; Dong, Xiumei (Frontiers in Veterinary Science, 2025)
Newborn piglet diarrhea caused by enterotoxigenic Escherichia coli (ETEC) causes serious economic losses in the swine industry worldwide. Heat-stable enterotoxins (STa) secreted by ETEC can damage the intestine, resulting in villus atrophy and shedding, which is the main cause of diarrhea in newborn piglets; however, the mechanism is not clear. This experiment was conducted in vivo (three-day-old suckling mice) and in vitro (IPEC-J2 cells) to explore the effect of STa on the intestinal epithelium by comparing the differences after infection with STa toxin-secreting E. coli O142 or STa-knockout E. coli O142ΔestA. The results showed that STa caused diarrhea, small intestinal edema, atrophy and rupture of small intestinal villi, and death in a dose-dependent manner in mice, and downregulated oxidative phosphorylation (OXPHOS) in IPEC-J2 cells. Activation of the mitochondria-mediated cell apoptosis pathway through excessive reactive oxygen species (ROS) production induces injury of the small intestinal villi, leading to diarrhea in piglets.